2015
DOI: 10.1126/science.aaa5612
|View full text |Cite
|
Sign up to set email alerts
|

The DNA damage response induces inflammation and senescence by inhibiting autophagy of GATA4

Abstract: Cellular senescence is a terminal stress-activated program controlled by the p53 and p16INK4a tumor suppressor proteins. A striking feature of senescence is the senescence-associated secretory phenotype (SASP), a pro-inflammatory response linked to tumor promotion and aging. We have identified the transcription factor GATA4 as a senescence and SASP regulator. GATA4 is stabilized in cells undergoing senescence and is required for the SASP. Normally, GATA4 is degraded by p62-mediated selective autophagy, but thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
680
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 761 publications
(748 citation statements)
references
References 66 publications
34
680
2
1
Order By: Relevance
“…GATA4 was identified as the key mediator of SASP, which was activated by damaged DNA and able to influence multiple tissue‐remodeling in a context‐dependent manner 12. In this study, we observed increased cardiomyocytes with damaged DNA based on γ‐H2AX immunostaining in postinfarction hearts (Figure 2A).…”
Section: Resultssupporting
confidence: 50%
See 4 more Smart Citations
“…GATA4 was identified as the key mediator of SASP, which was activated by damaged DNA and able to influence multiple tissue‐remodeling in a context‐dependent manner 12. In this study, we observed increased cardiomyocytes with damaged DNA based on γ‐H2AX immunostaining in postinfarction hearts (Figure 2A).…”
Section: Resultssupporting
confidence: 50%
“…Masson staining and dual immunofluorescence staining were included to establish that cardiomyocytes underwent senescence after hypoxia. Regarding its functional role, SASP was important for senescence to participate in tissue remodeling that was maintained by transcription factor GATA4 12. In this study, we noticed an increase of GATA4 accumulation in the border zones, where the senescence markers are also highly expressed.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations